Maturity Assessment of Knowledge Management Strategy and Implementation at Property Developer (International Journal of Scientific Research and Management (IJSRM), 2023)
Property and real estate industry is one of the fastest growing sectors in Indonesia’s macroeconomic development. In many countries, it is frequently used as an indicator of crisis as this industry is becoming an important sector of the country. Because it opens up opportunities that lead to Indonesia’s revenue (gross domestic product). In Indonesia, Astra Group is fully dedicated to ensuring the long-term success of its business and strives to be a source of pride for the nation. As part of its commitment, Astra Group expanded its operations into the property sector in 2013, leading to the establishment of Astra Property, which is the focus of this research. Astra Property is determined to raise the standards of property development across all segments, making a positive contribution to the quality of life and society as a whole. The company’s vision is to become the most preferred and trustworthy property company. In order to carry out its daily business activities, Astra Property has established a set of values and a culture that are expected to be embraced by both management and employees. However, given the nature of the property industry, it is crucial for Astra Property to effectively maintain and manage its knowledge resources. This becomes even more important considering factors such as employee turnover, the influx of new hires, and the need for agility within the organization. Surprisingly, no assessment has been conducted to evaluate the current state of knowledge management within Astra Property. Based on the survey results utilizing the APO KM Maturity Assessment tool, the total score obtained for Astra Property is 138.98. This indicates that Astra Property has implemented knowledge management on a company-wide scale, but standardization and formalization are yet to be achieved. There are several things that Astra Property can do to improve their current conditions : establish a knowledge-sharing culture, create a centralized knowledge repository and system, Implement knowledge capture processes, encourage continuous learning, and measure and evaluate knowledge management efforts by develop metrics and key performance indicators (KPIs) to assess the effectiveness of knowledge management practices.